2000
DOI: 10.1001/jama.283.22.2941
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Symptom-Onset-to-Balloon Time and Door-to-Balloon Time With Mortality in Patients Undergoing Angioplasty for Acute Myocardial Infarction

Abstract: The relationship in our study between increased mortality and delay in door-to-balloon time longer than 2 hours (present in nearly 50% of this cohort) suggests that physicians and health care systems should work to minimize door-to-balloon times and that door-to-balloon time should be considered when choosing a reperfusion strategy. Door-to-balloon time also appears to be a valid quality-of-care indicator. JAMA. 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
571
12
28

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,086 publications
(635 citation statements)
references
References 50 publications
24
571
12
28
Order By: Relevance
“…Additional meta-analysis data suggest that major adverse cardiac events increase with prolonged time to hospital presentation in patients receiving fibrinolysis, but that prolonged STB times minimally influence infarct artery patency or survival outcomes following primary PCI. 6 The above data have focused most primary PCI quality improvement efforts toward reducing DTB times. 22,23 Still, other studies have highlighted the importance of STB times on STEMI outcomes.…”
Section: Primary Pci Delays and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Additional meta-analysis data suggest that major adverse cardiac events increase with prolonged time to hospital presentation in patients receiving fibrinolysis, but that prolonged STB times minimally influence infarct artery patency or survival outcomes following primary PCI. 6 The above data have focused most primary PCI quality improvement efforts toward reducing DTB times. 22,23 Still, other studies have highlighted the importance of STB times on STEMI outcomes.…”
Section: Primary Pci Delays and Mortalitymentioning
confidence: 99%
“…3,5 Despite this recommendation, achieving primary PCI within 90 minutes has proven to be an elusive goalespecially for patients presenting to hospitals without PCI capability. Although some studies have suggested that time to reperfusion is less important for PCI than fibrinolysis, 6,7 most studies have demonstrated that treatment delays to primary PCI are associated with increased mortality 8 -13 and larger infarct size. 14 Prior studies, however, differ on whether the total ischemic interval between symptom onset and PCI reperfusion, so-called symptom-to-balloon (STB) time best predicts mortality, or whether mortality is more strongly determined by the duration between hospital arrival and performance of primary angioplasty, the so-called door-toballoon (DTB) time.…”
mentioning
confidence: 99%
“…Timely response and early PCI during the “golden hour” (60 minutes) has been shown to decrease morbidity and mortality associated with AMI 4, 5, 6. Driving time to a PCI‐capable hospital is an important factor in the timely response to this life‐saving intervention 5, 7. A study by Nallamothu and colleagues found that nearly 80% of the US population lived within 60 minutes to a PCI‐capable hospital with a median driving time of 11.3 minutes 8.…”
Section: Introductionmentioning
confidence: 99%
“…Shorter doorto-balloon (D2B) time has strong association with a lower mortality rate [3][4][5]. Based on these data, a D2B time of \90 min has been established as a Class I recommendation in the current guidelines [6,7].…”
Section: Introductionmentioning
confidence: 99%